(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suryanti IAP, Purnamasari MI, Prihatna C, Rusmana I, Wahyudi AT, Suwanto A. 2024. Characterization of endophytic bacterial isolates from oil palm (Elaeis guineensis) seedlings and ramets for their plant growth-promoting potential. Biodiversitas 25: 3775-3788. Using sterile tissue culture to cultivate oil palm (Elaeis guineensis Jacq.) seedlings results in the loss of beneficial endophytic bacteria, which can lead to various growth issues, including abnormal flower development and reduced palm oil production. The study aimed to investigate the potential endophytic bacteria in oil palm seedlings and ramets that serve as plant growth promoters. This research began with isolating and characterizing bacterial isolates with plant growth-promoting traits, then identification using 16S rRNA gene sequencing. In vitro and in vivo growth tests were carried out to assess the prospects of these bacterial isolates. Seventeen bacterial isolates were successfully cultured from oil palm seedlings and ramets (seedlings from tissue culture), with 12 and 5 isolates, respectively, which displayed characteristics of plant growth-promoting bacteria: 88% could produce aminocyclopropane-1-carboxylate (ACC) deaminase, 18% exhibited nitrogen-fixing abilities, 47% demonstrated phosphate solubilization, and 12% were producers of indole-3-acetic acid (IAA) hormone, which. One of the isolates, designated as 3AK, was indicated as the Aeromonas genus, which originates from the environment and has all the plant growth-promoting properties tested qualitatively in this study. In vitro growth testing showed that 3AK isolate had the most significant average lengths for both shoots (4.4±0.4 cm) and roots (8.2±0.5 cm). In the greenhouse experiment (in vivo), the oil palm seedlings treated with bacteria, such as 3AK, exhibited differences in shoot and root dry weight compared to the control group, and the difference was statistically significant. These findings collectively indicate that endophytic bacteria code 3AK is isolated from oil palm root, identified as Aeromonas taiwanensis through 16S rRNA gene sequencing, and has the potential as a plant growth promoter. Inoculation of Aeromonas taiwanensis strain 3AK and PsJN as Burkholderia phytofirmans strain PsJN (already known as a model for promoting plant growth) was carried out for the first time on the growth of oil palm seedlings.